2018
DOI: 10.5195/emaj.2018.147
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Intrapreneurship Growth in Nigeria: Evidence from Selected Manufacturing Firms

Abstract: The study examines the effect of organizational culture (measured by organizational norms and organizational shared values) on intrapreneurship growth in manufacturing sector of the Nigerian economy. Survey research design was used through the administration of structured questionnaire to members of staff of Nestle Nigeria PLC and PZ Cussons Nigeria PLC. The population of the study consist 2325 and 3500 staff of Nestle Nigeria PLC and PZ Cussons Nigeria PLC respectively. Using the Raosoft sample size determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…No organization can thrive and survive unless it is able and capable to nurture talents that are capable of creativity and innovative performance in addition to technological forces. For instance, Eze, Abdul, Nwaba and Adebayo (2018) argue that it is actually with the support of intrapreneurs that many organizations are able to transform their dreams into realities in the form of goals accomplished. Thus, organizations perceive intrapreneurs as catalysts through which organizations achieve certain goals and objectives.…”
Section: Organisational Greening Behavioural Change (Ogbc)mentioning
confidence: 99%
See 1 more Smart Citation
“…No organization can thrive and survive unless it is able and capable to nurture talents that are capable of creativity and innovative performance in addition to technological forces. For instance, Eze, Abdul, Nwaba and Adebayo (2018) argue that it is actually with the support of intrapreneurs that many organizations are able to transform their dreams into realities in the form of goals accomplished. Thus, organizations perceive intrapreneurs as catalysts through which organizations achieve certain goals and objectives.…”
Section: Organisational Greening Behavioural Change (Ogbc)mentioning
confidence: 99%
“…2.0 THEORETICAL REVIEW Several theories attribute individuals' willingness to do things differently, such as an attitudinal and behavioural change to the intrapreneurship characteristics in an organisational set-up (Eze et al, 2018). Although motivation has a way of directing one's behaviour towards particular goal attainment, it begins from a felt need to perform certain behaviours to enhance productivity or effectiveness.…”
Section: Strategy Implementation Stagementioning
confidence: 99%
“…Third, various studies [112][113][114][115][116] have explored other factors, such as organizational culture, vision, team management, compensation, market orientation, flexibility, and job satisfaction, as antecedents of intrapreneurial orientation. These studies revealed that these factors play an essential role in facilitating intrapreneurship actions.…”
Section: Relationship Between Learning Organization and Intrapreneurshipmentioning
confidence: 99%
“…Also, the significant role of recruitment and training process on innovation infrastructure cannot be neglected (Fernando, 2013). Adaptation of strategic human resources management application is not only prominent for innovation performance, but also is a driving force for intrapreneurship orientation (Messermith & Wales, 2013) which leads employee creativity and innovation potential to be volunteer to take responsibility in organizational goal (Eze et al, 2018).…”
Section: Strategic Intrapreneurshipmentioning
confidence: 99%